Analisis Kontribusi Nilai Teknologi Informasi Terhadap Kinerja Proses Bisnis Dan Dinamika Bersaing: Studi Empiris pada Hotel Berbintang di Surabaya - Oyong Lisa; Sihwahjoeni Sihwahjoeni (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
This study aimed to analyze the effect of information technology on business process performance, analyzing the effect of information technology on competitive dynamics, analyze the effect of business process performance against competitive dynamics, and analyze the impact of information technology on the dynamics of competing through business process performance. This research is explanatory research. The population in this study is the manager of information technology users totaling 276 people. The number of samples in this study as many as 164 people. The sampling technique using simple random sampling. Data analysis technique used is structural equation modeling (SEM). The analysis showed that information technology is positive and significant effect on the performance of business processes. Information technology and significant positive effect on the dynamics of competition. Business process performance and significant positive effect on the dynamics of competition. Business process performance mediates the effect of information technology againts competitive dynamics.